Sustainable urban homes? An assessment proposal in a community in the southeast of Mexico - Meza-Alvarez, Javier Aarón (2024)
[Introduction]: The sustainability of homes is one of the most significant challenges today. Activities that accelerate environmental degradation are developed on them: poor disposal of urban solid waste, excessive consumption of electricity and water, and use of fossil fuels, among others. [Objective]: To determine the level of sustainability of urban households in the municipality of Macuspana, Tabasco, Mexico. [Methodology]: 370 urban households representative of the total number of urban dwellings inhabited in the city were evaluated, with a confidence level of 95 %. A Sustainability Assessment Framework for Urban Households (MESHU) created from the selection, measurement, and percentage ratio of social, economic, and environmental indicators is proposed. 30 sustainability indicators divided into the following attributes were evaluated: self-management, adaptability, environmental culture, coexistence and productivity. [Results]: The sustainability level of the homes was 45 %. In summary, they are pretty sustainable. [Conclusions]: The sustainability evaluation of urban homes allowed an approximation of the reality of the practices and use of natural resources in daily life. At the same time, it is evident that homes have a culture toward sustainability.